A Zn(II)-based 1D coordination polymer: Temperature-induced SCSC transformation and selective sorption of Congo Red. (1st November 2018) - Gu, Jia-Hui; Li, Wu-Xiang; Li, Hong-Xi; Li, Hai-Yan; Lang, Jian-Ping
Graphical abstract: Upon heating, [1, 4-bpebH2 ][Zn(H2 O)(1, 3, 5-HBTC)(μ-1, 3, 5-HBTC)]·2H2 O n (1 ) undergoes a SCSC transformation into [1, 4-bpebH2 ][Zn(1, 3, 5-HBTC)(η, η, η, -μ3 -1, 3, 5-HBTC)]·1.5H2 O n (2 ) in which the anionic single chain of1 is converted into the anionic ladder chain of2 through replacing the coordinated-H2 O molecules by μ-1, 3, 5-HBTC 2− ligands. Both1 and2 exhibit an excellent sorption performances towards CR in water. Abstract: Solvothermal reaction of Zn(NO3 )2 ·6H2 O with 1, 4-bis(2-(pyridin-4-yl)vinyl)benzene (1, 4-bpeb) and 1, 3, 5-benzenetricarboxylic acid (1, 3, 5-H3 BTC) (molar ratio = 1:1:3) at 120 °C in CH3 CN/H2 O (v/v = 1:2) produced a one-dimensional (1D) coordination polymer [1, 4-bpebH2 ][Zn(H2 O)(1, 3, 5-HBTC)(μ-1, 3, 5-HBTC)]·2H2 O n (1 ; [1, 4-bpebH2 ] 2+ = 4, 4′-(-1, 4-phenylenebis(ethene-2, 1-diyl))bis(pyridin-1-ium)) in 64% yield. Heating1 at 160 °C for 5 h gave rise to another 1D coordination polymer [1, 4-bpebH2 ][Zn(1, 3, 5-HBTC)(η, η, η, -μ3 -1, 3, 5-HBTC)]·1.5H2 O n (2 ) in a quantitative yield. Compounds1 and2 were characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis, powder X-ray diffraction, and single-crystal X-ray diffraction. Compound1 consists of [Zn(H2 O)(1, 3, 5-HBTC)] units which are interlinked by μ-1, 3, 5-HBTC 2− ligands to form a 1D [Zn(H2 O)(1, 3, 5-H2 BTC)(μ-1, 3, 5-HBTC)] n 2 n – anionic chain with [1, 4-bpebH2 ] 2+ cations located in-between these chains. Compound2 contains [Zn2 (1, 3, 5-HBTC)2 ] units which are interconnected to yield a 1D ladder-type [Zn(1, 3, 5-HBTC)(η, η, η-μ3 -1, 3, 5-HBTC)] n 2 n – with [1, 4-bpebH2 ] 2+ cations positioned in-between these chains. Upon heating, the anionic single chain structure of1 undergoes a single-crystal-to-single-crystal topological transformation into the anionic ladder-shaped chain structure of2 by replacing the coordinated water molecules in one chain via one μ-1, 3, 5-HBTC 2− ligand in the other chain in1 . Both compounds exhibit excellent sorption performance towards Congo Red (CR) in water at room temperature with the maximum absorption capacity of 2020 mg g −1 (1 ) or 2320 mg g −1 (2 ). Compound1 as a representative example can selectively absorb CR from its combination with selected cationic dyes in water.